Harga Diri dan Kesepian pada Mahasiswa Pengguna Media Sosial - Ulfa Hasbiah; Rijal Abdillah; Andreas Corsini Widya Nugraha (Departement of Mathematics Education, 2023)
Students tend to try a lot of new things that they have never tried before and have a high curiosity about many things. Various activities such as doing assignments, discussions, seminars, organizations and volunteer activities that are currently mostly carried out virtually make students feel less emotionally attached to other individuals and cause feelings of loneliness. The purpose of this study was to determine whether there is a relationship between self-esteem and loneliness in social media users. This research uses correlational quantitative method. Respondents in this study were college students of Bhayangkara Jakarta Raya University at Bekasi aged 18-24 years who actively communicated using social media at least two of the following social media, namely WhatsApp, Instagram, Twitter, and Facebook. The data collection technique used purposive sampling technique with 144 college students as respondents. Based on the results of the non-parametric Spearman's Rho there was a relationship of 0.999** with a significance of 0.000 (p<0.001). These results indicate a relationship with a significant positive correlation between self-esteem and loneliness in social media users at Bhayangkara Jakarta Raya University. Which mean, the higher self-esteem in college students, the higher college students who experience loneliness, and vice versa. Suggestions for further researchers are to explore the virtual communication phenomenon that is currently occurring in relation to loneliness and self-esteem and can examine other factors such as birth order, personality type, and others.